Gerontology Curriculum in the Aisyiyah Senior School (ASS) Program in Condong Catur Sleman - 'Aabidah Ummu 'Aziizah (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2024)
This research analyses the gerontology curriculum at Aisyiyah Senior School in Condong Catur. Through a qualitative approach, this study aims to understand how the gerontology curriculum is designed and implemented in the context of senior education. Data was collected through observation, in-depth interviews with teaching staff, and curriculum document studies. The research results indicate that the gerontology curriculum at this school has been designed considering the unique needs of senior learners, focusing on improving their quality of life through continuing education. These findings provide important insights into how senior education can be tailored to meet the needs and aspirations of older generations. The results show that the gerontology curriculum at Aisyiyah Senior School incorporates various essential aspects of senior life, including physical and mental health, social relationships, and participation in meaningful activities. This curriculum is designed to promote healthy and active ageing and enhance senior learners' quality of life. In addition, this school shows a solid commitment to a lifelong learning approach by providing opportunities for seniors to continue learning and growing. In conclusion, this study indicates that the gerontology curriculum at Aisyiyah Senior School is an effective model for senior education. These findings can provide valuable guidance for other institutions wishing to develop or improve their educational programs for older generations.